Effect of Online Business Learning, Parental, and Locus of Control on Online Entrepreneurship Interest in Vocational High School Students - Firda Aprian Ridwan; Baedhowi Baedhowi; Leny Noviani (Universitas Sebelas Maret, 2021)
This study aims to analyze the effect of online business learning, parental, and locus of control on online entrepreneurial interest in students of SMK Negeri 1 Karanganyar in the 2019/2020 academic year. The data analysis method used is descriptive quantitative, with primary and secondary data sources in the form of questionnaires and documentation. The population in this study were all students of class XI and XII on the competency of online business and marketing skills (BDP) with a sample of 105 students using the stratified proportion-tel random sampling technique. The results showed that there was a positive and significant influence between online business learning, parental, and locus of control on the interest in entrepreneurship simultaneously, with an F value of 43.529 and an R2 value of 56.4% with an effective contribution between online business learning (X1) 23 , 6%, parental (X2) 19% and locus of control (X3) 13.8%.